Nitrogen Uptake by Two Plants in Response to Plant Competition as Regulated by Neighbor Density - Jia, Xuan; Huangfu, Chaohe; Hui, Dafeng (Frontiers in Plant Science, 2020)
Plant species may acquire different forms of nitrogen (N) to reduce competition for the same resource, but how plants respond to neighbors with different densities in their N uptake is still poorly understood. We investigated the effects of competition regime on the uptake of different N forms by two hygrophytes, Carex thunbergii and Polygonum cripolitanum, by conducting a hydroponic test of excised roots and an in situ experiment in a subtropical wetland ecosystem. The two species were grown either in monocultures or mixtures with various neighbour densities. Root functional traits and N uptake rates of different N forms were measured. Our results showed that N uptake was mainly determined by N form, rather than species identity. Both species were able to use organic N sources, but they took up relatively more N supplied as NO3- than as NH4+ or glycine, irrespective of competition treatments. Both species preferred NO3- when grown in monoculture, but in the presence of competitors, the preference of fast-growing C. thunbergii persisted while P. criopolitanum acquired more NH4+ and glycine, with stronger responses being observed at the highest neighbour density. The hydroponic test suggested that these divergences in N acquisition between two species might be partially explained by different root functional traits. To be specific, N uptake rates were significantly positively correlated with root N concentration and specific root length, but negatively correlated with root dry matter content. Our results implicated that C. thunbergii has a competitive advantage with relatively more stable N acquisition strategy despite a lower N recovery than P. cripolitanum, whereas P. cripolitanum could avoid competition with C. thunbergii via a better access to organic N sources, partly mediated by competition regimes.